2017
DOI: 10.1111/exd.13321
|View full text |Cite
|
Sign up to set email alerts
|

Mutational profiling of acral melanomas in Korean populations

Abstract: The proportion of acral melanoma (AM) is much higher in Asian populations than in Caucasian populations. Although mutational profiles associated with AM have been discovered in Caucasian populations, knowledge of its genetic alterations in Asian populations is limited. To describe the molecular nature of AM in Korean patients, we performed mutational profiling of AM and matched normal tissues in patients. Fifty-one formalin-fixed paraffin-embedded AM samples and 32 matched pairs from patients' saliva DNA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 56 publications
(87 reference statements)
1
22
4
1
Order By: Relevance
“… In contrast, the NRAS mutation rates in AMs reported in this study were similar to those described in other Asian studies. Compared with the overall results from Asian populations, KIT and KRAS mutations were found to be more prevalent in AMs in our study population . In addition to underlying ethnic disparities, these differences may have been due, in part, to the AMs in our study being composed of only acral lentiginous melanomas.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… In contrast, the NRAS mutation rates in AMs reported in this study were similar to those described in other Asian studies. Compared with the overall results from Asian populations, KIT and KRAS mutations were found to be more prevalent in AMs in our study population . In addition to underlying ethnic disparities, these differences may have been due, in part, to the AMs in our study being composed of only acral lentiginous melanomas.…”
Section: Discussionsupporting
confidence: 90%
“…However, AMs account for 50–70% of all cases of melanoma in Asians . Although several genomic profiling studies of melanoma have been conducted, the number of AM cases in those studies was limited . Furthermore, a comprehensive comparison of genomic alterations between AMs and nonacral melanomas (NAMs) in Asians has not been conducted, and the associations between structural variants and clinical outcomes have not been characterized.…”
mentioning
confidence: 99%
“…Thus, mutation was not found to be associated with a specific anatomical site on the plantar surface. Our study showed a much higher frequency of BRAF V600E mutations in acral melanoma than was found in previous Asian studies (Jin et al, 2013;Sakaizawa et al, 2015;Shim et al, 2017;Si et al, 2012). These differences might be explained by the improvement in detection tools, by the selection of deeper melanomas showing variable cytology and mixed cellularity of various morphologies, and by the genes included in the test panels.…”
Section: Discussioncontrasting
confidence: 55%
“…Although other studies of SUM present a higher percentage of 30-50% [25,32] or no detected among 13 SUM patients [29]. In HFM/ALM, KIT mutations are frequent -occurring in 8.5-36% of tumors usually as a substitution of a single amino acid in exon 11, 13, or 17 [6,[8][9][10][30][31][32][33][34]. Siroy et al sequenced 54 patients with advanced acral melanoma and reported KIT mutation in 11% of cases [5].…”
Section: Kitmentioning
confidence: 98%